An inclusive Research and Education Community (iREC) model to facilitate undergraduate science education reform - Monti, Denise L.; Gill, Julia C.; Adair, Tamarah L.; Adams, Sandra D.; Ahumada-Santos, Yesmi Patricia; Amaya, Isabel; Anders, Kirk; Anderson, Justin R.; Antunes, Mauricio S.; Ayuk, Mary; Baliraine, Frederick; Bates, Tonya C.; et al. (Frontiers in Education, 2024)
Over the last two decades, there have been numerous initiatives to improve undergraduate student outcomes in STEM. One model for scalable reform is the inclusive Research Education Community (iREC). In an iREC, STEM faculty from colleges and universities across the nation are supported to adopt and sustainably implement course-based research -a form of science pedagogy that enhances student learning and persistence in science. In this study, we used pathway modelling to develop a qualitative description that explicates the HHMI Science Education Alliance (SEA) iREC as a model for facilitating the successful adoption and continued advancement of new curricular content and pedagogy. In particular, outcomes that faculty realize through their participation in the SEA iREC were identified, organized by time, and functionally linked. The resulting pathway model was then revised and refined based on several rounds of feedback from over 100 faculty members in the SEA iREC who participated in the study. Our results show that in an iREC, STEM faculty organized as a long-standing community of practice leverage one another, outside expertise, and data to adopt, implement, and iteratively advance their pedagogy. The opportunity to collaborate in this manner and, additionally, to be recognized for pedagogical contributions sustainably engages STEM faculty in the advancement of their pedagogy.Here, we present a detailed pathway model of SEA that, together with underpinning features of an iREC identified in this study, offers a framework to facilitate transformations in undergraduate science education.